Task reminder system via sms - Noor Syafika, Jamaludin (2012)
Time management techniques say that it's better to keep track of tasks using a reminder system rather than your memory.Owing to intensive agenda,working person may have dozens of works and others tasks that should be done and it is normal that even people with much trained memory cannot remember everything.This is a critical problem which caused difficulty to staffs and lecturers of FSKKP for alerts on important messages received.This is because too many messages received in their email at the same time making it look unorganized.The purpose of this study is proposing a Task Reminder System via SMS.The system enables staffs and lectures to get reminder about their task due to the important of the message.Other than that,the system is using SMS application to give alertness to the staffs and lecturers about their task.Hopefully,with the Task Reminder System,it will help the staffs and lecturers of FSKKP to manage their task wisely and perform in the work better.